THE INFLUENCE OF LIQUIDITY, PROFITABILITY, AND SOLVENCY ON BANKING STOCK PRICE LISTED ON IDX FOR THE 2015-2019 PERIOD - Kiran Raj; Narti Eka Putri (Management and Leadership Study Programme, 2021)
This quantitative research aims to determine the effect of liquidity, profitability and solvency on stock prices. The type of data used is secondary data obtained from the Indonesia Stock Exchange website and the Yahoo Finance website. A total of 38 banking companies listed on the IDX from 2015-2019 were sampled based on purposive sampling and processed using SPSS version 23 software. The variables used in the research were liquidity, profitability and solvency as well as stock prices. The partial results of this study indicate that liquidity and solvency have a significant effect on stock prices while solvency has no significant effect on stock prices. And the results together also show that liquidity, profitability, and solvency have a significant effect on stock prices.